The Effect of Interpersonal Skills, Intrapersonal Skills, Suprapersonal Skills, and Career Adaptability on Employability Skills in Indonesian Aviation Polytechnic Cadets - Aditiyawarman, M. Andra; Yulianto, Bambang; Suhartini, Ratna; ., Ekohariadi; Wrahatnolo, Tri (Journal of Ecohumanism, 2025)
This study aims to determine the influence effect of Interpersonal skills, Intrapersonal skills, Suprapersonal skills, and Career adaptability on Employability skills in Aviation Polytechnic Cadets. This research was conducted in seven official schools under the Indonesian Civil Aviation Human Resources Development Centre. The sample of this study amounted to 300 cadets who were determined using purposive random sampling. Data collection techniques consisted of distributing questionnaires and documentation. The data analysis technique in this study uses the Structural Equation Model (SEM), which consists of a measurement model and a structural model. The measurement model produces research constructs that fit the data. The structural model describes the causal or predictive relationship between exogenous and endogenous variables. The exogenous variables consist of Intrapersonal skills, Interpersonal skills, Suprapersonal skills, and Career adaptability. The endogenous variable is Employability skills. Structural model testing uses the SEM-PLS Program. The structural model analysis shows that the model fits significantly with the data, with the standardized regression coefficient (SRW) estimates being significant (p<0.001). The results showed: (1) There is a significant positive influence between Intrapersonal Skills on Career Adaptability; (2) There is a significant positive influence between Interpersonal Skills on Career Adaptability; (3) There is a significant positive influence between Suprapersonal Skills on Career Adaptability; (4) There is a significant positive influence between Career Adaptability on Employability Skills; (5) There is a significant positive influence between Intrapersonal Skills on Employability Skills through the mediator Career Adaptability; (6) There is a significant positive influence between Interpersonal Skills on Employability Skills through the mediator Career Adaptability; (7) There is a significant positive influence between Suprapersonal Skills on Employability Skills through the mediator Career Adaptability. The research implies that it is recommended that lecturers in teaching not only pay attention to academic aspects (cognitive) but also pay attention to other aspects such as Intrapersonal, Interpersonal, Suprapersonal, Employability, and Career adaptability.